THE INFLUENCE OF POLITICAL NEWS ATTITUDE AND PERCEIVED IMPORTANCE OF RELIGIOUS ON INTENTION TO SUPPORT PDIP AFTER 2024 INDONESIAN GENERAL ELECTION - Putra Baroto, Medio; Lukmantoro, Triyono; Surayya Ulfa, Nurist (Interaksi Online, 2024)
The phenomenon related to the intention of public support for the Indonesian Democratic Party of Struggle (PDIP) is decreasing at a time when parties opposing it are increasing. Support intentions can be seen as a beneficial aspect for political parties from the perspective of human behavior in politics. Given the increasingly competitive political dynamics in Indonesia with the emergence of new parties, the decline in support for PDIP is a major concern. Although PDIP managed to win the 2024 Legislative Election, there was a significant drop in vote percentage compared to the previous election, as well as the failure of its presidential and vicepresidential candidate pair (Ganjar-Mahfud) in the 2024 Executive Election. The shifting dynamics of Indonesian politics provide the context for this research, with PDIP, one of the main political parties, facing a drop in electability despite winning the 2024 parliamentary election. This drop-in support is assumed to be impacted by poor government performance, the formation of new parties, and a variety of campaign techniques that are less effective. The paradigm of this research is positivism with quantitative approach. This study aims to explain the effect of political news attitude and perceived importance of religious on intention to support PDIP by using the theory of planned behavior. The population in this study were political participants from generation z, with a non-probability sampling technique on 100 both male and female respondents aged 18-30 years who participated in the 2024 elections and had contact with a political party, namely PDI-Perjuangan or PDIP. The results of hypothesis testing using multiple linear regression tests show that the influence of political news attitude and perceived importance of religious has an influence on intention to support PDIP after the 2024 Indonesian General Election.